Tissue Doppler Imaging of the Diaphragm in Healthy Subjects and Critically Ill Patients - Soilemezi, Eleni; Savvidou, Savvoula; Sotiriou, Panagiota; Smyrniotis, Dimitrios; Tsagourias, Matthew; Matamis, Dimitrios (American journal of respiratory and critical care medicine, 2020)
Tissue Doppler imaging (TDI) is an echocardiographic method that measures the velocity of moving tissue. We applied this technique to the diaphragm to assess the velocity of diaphragmatic muscle motion during contraction and relaxation. In 20 healthy volunteers, diaphragmatic TDI was performed to assess the pattern of diaphragmatic motion velocity, measure its normal values, and determine the intra- and interobserver variability of measurements. In 116 consecutive ICU patients, diaphragmatic excursion, thickening, and TDI parameters of peak contraction velocity, peak relaxation velocity, velocity-time integral, and TDI-derived maximal relaxation rate were assessed during weaning. In a subgroup of 18 patients, transdiaphragmatic pressure (Pdi)-derived parameters (peak Pdi, pressure-time product, and diaphragmatic maximal relaxation rate) were recorded simultaneously with TDI. In terms of reproducibility, the intercorrelation coefficients were >0.89 for all TDI parameters ( < 0.001). Healthy volunteers and weaning success patients exhibited lower values for all TDI parameters compared with weaning failure patients, except for velocity-time integral, as follows: peak contraction velocity, 1.35 ± 0.34 versus 1.50 ± 0.59 versus 2.66 ± 2.14 cm/s ( < 0.001); peak relaxation velocity, 1.19 ± 0.39 versus 1.53 ± 0.73 versus 3.36 ± 2.40 cm/s ( < 0.001); and TDI-maximal relaxation rate, 3.64 ± 2.02 versus 10.25 ± 5.88 versus 29.47 ± 23.95 cm/s ( < 0.001), respectively. Peak contraction velocity was strongly correlated with peak transdiaphragmatic pressure and pressure-time product, whereas Pdi-maximal relaxation rate was significantly correlated with TDI-maximal relaxation rate. Diaphragmatic tissue Doppler allows real-time assessment of the diaphragmatic tissue motion velocity. Diaphragmatic TDI-derived parameters differentiate patients who fail a weaning trial from those who succeed and correlate well with Pdi-derived parameters.